Gene fusions characterize a subset of uterine cellular leiomyomas. Issue 12 (24th August 2020) - Hodgson, Anjelica; Swanson, David; Tang, Shangguo; Dickson, Brendan C.; Turashvili, Gulisa
Abstract: Uterine leiomyomas are the most common benign tumor of the female genital tract. Previous studies have shown that conventional leiomyomas often harbor‐specific alterations including rearrangements involving HMGA2 . Cellular leiomyomas are a variant of uterine leiomyoma that are less well‐studied from a genomic point of view. Morphologically and immunohistochemically, cellular leiomyomas may be confused with low‐grade endometrial stromal neoplasms, a group of tumors which frequently harbor a number of recurrent gene fusions. Ancillary molecular testing may be used to investigate tumors where low‐grade endometrial stromal neoplasms enter into the differential diagnosis. At our institution, we identified a uterine cellular leiomyoma harboring a HMGA2‐TRAF3IP2 fusion. After a retrospective review 11 additional tumors were identified. All included cases were reviewed and evaluated for immunohistochemical expression of smooth muscle actin, desmin, h‐caldesmon, CD10, estrogen receptor, and progesterone receptor. RNA sequencing using the TruSight RNA Fusion Panel was performed on formalin‐fixed paraffin‐embedded tissue samples. In addition to the index case, two other cases harbored fusions: HMGA2‐NAA11 and TPCN2‐YAP1, of which the latter is novel and was confirmed with reverse transcriptase‐polymerase chain reaction. In conclusion, a subset of cellular leiomyomas harbor rearrangements involving HMGA2, suggesting molecular kinship with conventional uterine leiomyomas. In addition, the prevalence of the novel TPCN2‐YAP1 gene fusion in cellular leiomyomas requires further study. The fusions reported here, when identified, may be useful when the diagnosis of cellular leiomyoma is in question.